2021
DOI: 10.1007/s11103-021-01170-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling cassava production and pest management under biotic and abiotic constraints

Abstract: Key message We summarise modelling studies of the most economically important cassava diseases and arthropods, highlighting research gaps where modelling can contribute to the better management of these in the areas of surveillance, control, and host-pest dynamics understanding the effects of climate change and future challenges in modelling. Abstract For over 30 years, experimental and theoretical studies have sought to better understand the epidemiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 173 publications
(298 reference statements)
1
7
0
Order By: Relevance
“…Cassava is known to harbor fungal genera belonging to many species as endophytes and/or plant pathogens [32][33][34][35]. Our study confirmed this as we isolated pathogenic fungi from Alternaria, Elsinoë, Neofusicoccum, Fusarium, Mycosphaerella, and Colletotrichum genera, among others.…”
Section: Discussionsupporting
confidence: 83%
“…Cassava is known to harbor fungal genera belonging to many species as endophytes and/or plant pathogens [32][33][34][35]. Our study confirmed this as we isolated pathogenic fungi from Alternaria, Elsinoë, Neofusicoccum, Fusarium, Mycosphaerella, and Colletotrichum genera, among others.…”
Section: Discussionsupporting
confidence: 83%
“…This aligns with the results of the study where most farmers responded as never having encountered CBB. The ignorance might be because more focus has been placed on other cassava diseases at the expense of CBB revealed by the fact that most farmers in the study could easily identify other cassava pests and diseases and even relate them to their respective symptoms [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Cassava pests remain a signi cant challenge for cassava farmers in Asia because of the pest complex nature of these pests. The availability of molecular identi cation tools such as DNA Barcoding is increasingly essential to support cassava pest management, leading to reduced cassava pest damage (Bellotti, 2001;Chavez et al, 2021;Paul et al, 2022;Bisimwa et al, 2019). The molecular identi cation of these pests contributes to our understanding of the arthropod community associated with cassava and serves as a valuable resource of molecular data.…”
Section: Discussionmentioning
confidence: 99%